Design of Multi-Epitope Peptide Vaccine Against Malaria Plasmodium falciparum Ripr Using in Silico Approach - Omnia Abdelazim, Rawan Nasreldin Alsharif (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Malaria is still the most serious public health problem in tropical and subtropical regions. There are different challenges in the progression of the vaccine. Malaria caused by Plasmodium falciparum is more common than that caused by other types of Plasmodium. This study aims to design of multi-epitope peptide vaccine against malaria Plasmodium falciparum RH 5 interacting protein ( PfRipr ) using in silico approach between July and November 2022. Conserved PfRipr sequences were analyzed from the National Centre for Biotechnology Information (NCBI). Then the candidate epitopes were analyzed by different prediction tools from the Immune Epitope Database IEDB analysis resource. The prediction tools selected are B-cell epitope prediction to predict linearity, surface accessibility, and immunogenicity by using BePipred, emini surface accessibility, Kolaskar, and Tongaokar, respectively. T cell epitope prediction tools were used to predict epitopes binding to MHC I and MHC II alleles, and population coverage calculation tools to estimate the coverage of promising epitopes. Finally, PfRipr was searched at the Uniprot website, and the resulting PDB file was applied to the Chimera software to visualize the 3D structure. PfRipr showing activation of T cell more than B cell, the three most promising epitopes bind to 14, 11,11 different alleles of MHC I and 27,22,21 different alleles of MHC II. The combination of the six promising epitopes binding to MHC I and MHC II illustrated respectable results in population coverage calculation, which were 99.65% in the whole world and 98.87% in Sudan. We expect that these multiple epitopes could aid in the development of a vaccine that can help in the fight against malaria. Being a potential target for in vivo and in vitro studies.